2018
DOI: 10.4132/jptm.2018.04.28
|View full text |Cite
|
Sign up to set email alerts
|

Hyalinizing Trabecular Tumor of the Thyroid Gland, a Diagnostic Challenge in Fine-Needle Aspiration Cytology: Case Report

Abstract: Hyalinizing trabecular tumor (HTT) is a rare thyroid tumor with low to minimal malignant potential. HTT is often misinterpreted as other thyroid tumors, including papillary thyroid carcinoma (PTC) and medullary thyroid carcinoma (MTC), on fine-needle aspiration (FNA) cytology, because of its overlapping cytologic features, such as nuclear grooves and intranulcear pseudoinclusions. Although cytopathologists cannot definitely conclude HTT by FNA cytology, suspicion of HTT is necessary to avoid misdiagnosing HTT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The challenges to solving the problem of presurgical diagnostics are 3‐fold: First, some of the key cytologic features of PTC and medullary thyroid carcinoma, such as enlarged oval nuclei, nuclear grooves, and intranuclear pseudoinclusions, are typically seen in HTT (Fig. ) . Tabulation of the cytology diagnoses standardized into the Bethesda System for Reporting Thyroid Cytopathology showed that 42.1% and 26.4% of HTT cases were diagnosed on FNA as suspicious for malignancy (Bethesda V) and malignant (Bethesda VI), respectively (Table ), which often triggered total thyroidectomy.…”
Section: Cytologic Challenges Resulting From Httmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenges to solving the problem of presurgical diagnostics are 3‐fold: First, some of the key cytologic features of PTC and medullary thyroid carcinoma, such as enlarged oval nuclei, nuclear grooves, and intranuclear pseudoinclusions, are typically seen in HTT (Fig. ) . Tabulation of the cytology diagnoses standardized into the Bethesda System for Reporting Thyroid Cytopathology showed that 42.1% and 26.4% of HTT cases were diagnosed on FNA as suspicious for malignancy (Bethesda V) and malignant (Bethesda VI), respectively (Table ), which often triggered total thyroidectomy.…”
Section: Cytologic Challenges Resulting From Httmentioning
confidence: 99%
“…Third, the relative rarity of HTT has limited the opportunity for general cytopathologists to become proficient in recognizing the key cytologic features this entity. Although the exact incidence is not known, the finding that 11 of 26 reports (42%) documenting the cytology of HTT are individual case reports is likely a reflection of its rarity . Therefore, heightened awareness of the subtle cytologic features of HTT and the availability of novel, specific molecular markers are important in the presurgical identification of this neoplasm.…”
Section: Cytologic Challenges Resulting From Httmentioning
confidence: 99%
“…The latter authors described a lesion with peculiar histological features composed of a trabecular growth pattern with prominent deposition of hyaline material. Following this description, several authors published case reports or small series demonstrating that HTT is essentially a benign neoplasm requiring conservative management, even though it is worth noting that very rare cases of invasive HTT have been described …”
Section: Introductionmentioning
confidence: 99%
“…The majority of histological series show that reaching the correct diagnosis of this neoplasm does not pose a diagnostic challenge . However, a review of the literature indicates that reaching the correct preoperative diagnosis of HTT is more elusive, as the correct interpretation was achieved in only 8% of cases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation